Reticulocyte hemoglobin content as a predictor of iron deficiency anemia - Ni Made Rini Suari; Ketut Ariawati; Nyoman Adiputra (Indonesian Pediatric Society, 2015)
Background Iron deficiency anemia (IDA) is the most common form of anemia in developing countries, such as Indonesia. Iron deficiency anemia in children is a serious problem because it affects their growth and development. Early detection of IDA and subsequent treatment in childhood may prevent future health problems.Objective To assess the use of reticulocyte hemoglobin content (CHr) to detect IDA in children aged 6-60 months.Methods We performed a cross-sectional study to measure the sensitivity and specificity of CHr compared to serum ferritin which is considered to be the gold standard for IDA diagnosis. The study was conducted from September 2011 to March 2013 in children aged 6-60 months who visited the Pediatric Outpatient Clinic, Sanglah Hospital, and Puskesmas II in West Denpasar. Data analysis was performed by 2x2 table. The results were assessed by area under the curve (AUC) and receiver operating characteristic (ROC).Results Of 121 children underwent blood testing during the study period, 69 children were excluded because they did not have hypochromic microcytic anemia, leaving 52 subjects eligible for the study. The prevalence of IDA in this study was 31%. Reticulocyte hemoglobin content (CHr) â‰¤ 23.1 pg had 88% (95%CI 71 to 100%) sensitivity and 25% (95%CI 11 to 39%) specificity.Conclusion Reticulocyte hemoglobin content < 23.1 pg may be a good predictor of IDA.